Only the workers can free the workers: the origin of the worker's control tradition and the Trade Union Advisory Coordinating Committee (TUACC), 1870-1979 - Ulrich, Nicole (My University, 2008)
With the rise of the new social movements and increasing number of protests over service delivery in South Africa’s poorest townships, many activists have started to question whether unions are able to relate to the demands of the unorganised and poor. It is argued that under the new democracy COSATU has become bureaucratic and is too closely aligned to the ANC to challenge government policies and play a transformative role in society. Such concerns are not entirely new. Labour historians and industrial sociologists have long debated the political potential and democratic character of trade unions and there is a vast literature documenting the organisational styles of unions in South Africa today and in the past. Based on examination of union archival records and interviews with key informants, this study traces the emergence of the ‘workers control’ tradition in South African trade unions. ‘Workers control’ is a unique approach based on non-racial, industrial trade unions, which are democratically organised on the factory floor. Such unions, which are ideally controlled by elected worker representatives at all levels and united nationally on the basis of sharing common policies and resources, create the basis for an autonomous movement that promotes the interest of workers. Although most closely associated with FOSATU (1979-1985), this study found that workers control had deeper historical roots. Workers control was a product of the ideological and organisational renewal that characterised the 1970s and was initially created by the Trade Union Advisory Coordinating Committee (TUACC) in Natal and, later, the Witwatersrand. TUACC, which included significant numbers of women employed as semi-skilled production workers and unskilled migrant men, reflected complex shifts in the labour market and the economy. It was in this context that ordinary union members together with a diverse layer of activists developed TUACC’s unique approach to organisation. The power of white university trained activists in determining union policies has been overestimated and worker leaders, particularly more educated women workers, played an important role in building TUACC unions. Based on a Gramscian analysis, TUACC maintained that democratic unions based on strong shop floor organisation could exploit loop holes in the law and participate in industrial structures without undermining union autonomy and democracy. TUACC, however, was less clear of how to relate to political movements and parties. TUACC distanced itself officially from the banned ANC to avoid repression, but some workers and unionists looked to homeland and traditional leaders for alliances. This tension between the creation of a democratic trade union culture and the workers’ support of more autocratic political and traditional leaders and populist movements was never resolved. All of TUACC’s affiliates were founder members of COSATU and this study gives us some insight into the traditions that inform COSATU’s responses to social movements, political parties and the state today. Drawing on the insights of the Anracho-syndicalism, this study also highlights some of the dangers of separating the economic and political activities of workers into unions and political parties respectively.
Keywords: Trade unions; African workers; 1973 strike wave; Federation of South African Tade Unions; Trade Union Advisory Coordinationg Council; Worker's control